MicroRNA-15a, microRNA-15b and microRNA-16 inhibit the human dopamine D1 receptor expression in four cell lines by targeting 3′UTR –12 bp to + 154 bp - Xue Wu; Feng-ling Xu; Xi Xia; Bao-jie Wang; Jun Yao (Artificial Cells, Nanomedicine, and Biotechnology)
Background The abnormal expression Dopamine D1 receptor (DRD1) gives rise to the dysfunction of dopaminergic neurotransmitter and may be associated with the occurrence of schizophrenia. MicroRNAs (miRNAs) can regulate the DRD1 expression by binding 3’UTR and be involved in the post-transcriptional regulation.Methods We first constructed the pmirGLO-recombined vectors of series of DRD1 gene 3′UTR-truncated fragments and performed the luciferase receptor assay to screen the underlying 3′UTR sequence targeted by miRNAs. Then, we predicted the potential miRNAs binding the target sequence and confirmed their effects using luciferase receptor assay after transfection of the miRNA mimics/inhibitors. We also examined the effects of the miRNA on the endogenous DRD1 expression.Results We found that the DRD1 3′UTR ranging from –12 to +1135 bp was essential for the post-transcriptional regulation of miRNAs. The deletion of –12 to +154 bp fragment significantly increased the luciferase expression but not the mRNA expression. The miRNA-15a, miRNA-15b and miRNA 16 affected DRD1 expression in HEK293, U87, SK-N-SH and SH-SY5Y cell lines.Conclusion The miRNA-15a, miRNA-15b and miRNA-16 inhibit the human dopamine D1 receptor expression by targeting 3′UTR –12 to +154 bp.HighlightsDRD1 3′UTR ranging from –12 to +1135 bp was essential for the post-transcriptional regulation of miRNAs.The deletion of –12 to +154 bp fragment significantly increased the luciferase expression but not the mRNA expression.The miRNA-15a, miRNA-15b and miRNA 16 affected DRD1 expression in different cell lines, respectively.